Disinformation and polarization in the algorithmic society. Online hate speech trilogy (vol. 1) (2024)
This is the first book of the Online Hate Speech Trilogy. It focuses on the relationship between disinformation, political polarisation, and virtual attacks involving toxic language. These phenomena are much more complex than they may initially appear, and they are strongly interrelated with each other in the algorithmic society. The authors analyse the deep origins of hate speech and its manifestations online. They highlight attacks against the LGBTQ+ community in Europe, journalists in Asia, and black politicians in Latin America. Additionally, these researchers examine the crucial role of fact-checking agencies in confronting toxic language and combating hate speech.